Use of six sigma metrics in assessing the performance of the ımmunonephometric device in C-reactive protein measurements - Sanem Karadag Gecgel; Sevim Esmedere Eren (Al Ameen Medical College, 2018)
Background: We carried out a study for the purpose of comparing the six sigma values of the C-reactive protein (CRP) assay measured by immunonephometry with references of different authorities' quality criterias and evaluating the performance of the devices in our laboratory. Methods: In our study, internal quality control data of the CRP test performed on two different Siemens BN ProSpec (Dade Behring, Derfield, IL) devices at Bursa Yuksek Ihtisas Training and Research Hospital. Results: According to Ricos 'desired Total allowable error (TEa) ratio'; all the sigma values of the CRP test in BN ProSpec-1 and BN ProSpec-2 nephelometry devices were calculated as> 6 σ in each of the three periods and the performance of the CRP test was notified as 'world class'. Also, the sigma value determined according to Ricos 'optimal TEa' ratio was 5.8 σ (3.90 to 8.48 σ in each period) on both devices and CRP test performance was defined as 'excellent'. Moreover, when we considered the ratio of Rilibak TEa, the mean sigma values were 3.9 σ (between 2.59 and 5.75 σ in all three periods) and the CRP test performance was identified 'good'. Conclusion: As a consequence, the performance of the CRP test with nephelometry was evaluated as 'good' when the Rilibak criteria with the lowest TEa values is taken into consideration. Therefore, it is necessary for the correct quality control analysis to establish the reference TEa% values of our country for the CRP test.